Management of it-based classrooms through smart laboratory real-time management system - Mohd. Aizaini Maarof; Abdul Samad Ismail, 1930-; Mazleena Salleh; Rashidah Kadir; Anazida Zainal, 1967-; Konvensyen Teknologi Pendidikan (ke-16 : 2003 : Melaka) (Skudai : Universiti Teknologi Malaysia, 2003)
39